2020
DOI: 10.2151/jmsj.2020-042
|View full text |Cite
|
Sign up to set email alerts
|

Probability Ellipse for Tropical Cyclone Track Forecasts with Multiple Ensembles

Abstract: Pacific as the Regional Specialized Meteorological Center (RSMC) (Regional Specialized Meteorological Center Tokyo-Typhoon Center 1989), has adopted probability circles to represent track uncertainty. A probability circle is defined as the domain that the center of a TC is expected to exist within at a given

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The origin, abscissa, and ordinate of the two‐dimensional coordinate system are defined as the t ‐hour ensemble mean, along‐track direction, and cross‐track direction, respectively. The along‐ and cross‐track coordinates are determined in the same manner as the along‐ and cross‐track errors (Heming, 2017; Leonardo & Colle, 2017; Peng et al., 2017), except that the best track positions were replaced by the ensemble means, as in Kawabata and Yamaguchi (2020) (see Figure S3 in Supporting Information ). The along‐track coordinate of the position of an EPS member is positive (negative) if the member is ahead of (behind) the ensemble mean, whereas the cross‐track value is positive (negative) if the ensemble member is to the right (left) of the mean forecast track.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The origin, abscissa, and ordinate of the two‐dimensional coordinate system are defined as the t ‐hour ensemble mean, along‐track direction, and cross‐track direction, respectively. The along‐ and cross‐track coordinates are determined in the same manner as the along‐ and cross‐track errors (Heming, 2017; Leonardo & Colle, 2017; Peng et al., 2017), except that the best track positions were replaced by the ensemble means, as in Kawabata and Yamaguchi (2020) (see Figure S3 in Supporting Information ). The along‐track coordinate of the position of an EPS member is positive (negative) if the member is ahead of (behind) the ensemble mean, whereas the cross‐track value is positive (negative) if the ensemble member is to the right (left) of the mean forecast track.…”
Section: Methodsmentioning
confidence: 99%
“…However, some extreme cases were indicated in the 96-hr and 120-hr forecasts, that is, the cross-track radius was more than four times the along-track radius (Figure S5 in Supporting Information S1). These cases typically result from track bifurcations in the track, as described by Kawabata and Yamaguchi (2020).…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
See 2 more Smart Citations
“…The TCs with tropical storm intensity or above (maximum sustained surface wind speed of 35 kt or above) were taken into consideration. Note that there are several organizations that maintain their own historical TC records for the WNP basin (e.g., JTWC, JMA, the Hong Kong Observatory (HKO) of China, and CMA_STI), but previous studies have suggested that the differences in TC tracks and TC genesis are generally small, particularly in the satellite-observation areas [19][20][21][22]. To further improve our analyses, we used the three best track data sets available from the JTWC, CMA_STI, and JMA, and found consistent results for the record high TC frequency in November 2019.…”
Section: Datamentioning
confidence: 99%